The Relationship Between Socioeconomic Status and Scalp Event-Related Potentials: A Systematic Review - Perera-W.A., Hiran; Salehuddin, Khazriyati; Khairudin, Rozainee; Schaefer, Alexandre (Frontiers in Human Neuroscience, 2021)
Several decades of behavioral research have established that variations in socioeconomic status (SES) are related to differences in cognitive performance. Neuroimaging and psychophysiological techniques have recently emerged as a method of choice to better understand the neurobiological processes underlying this phenomenon. Here we present a systematic review of a particular sub-domain of this field. Specifically, we used the PICOS approach to review studies investigating potential relationships between SES and scalp event-related brain potentials (ERP). This review found evidence that SES is related to amplitude variations in a diverse range of ERPs: P1, N1, N2, Error-Related Negativities (ERN), N400, auditory evoked potentials, negative difference waves (Nd), P3 and slow waves (SW). These ERPs include early, mid-latency and late potentials that reflect a broad range of cognitive processes (e.g. automatic attentional processes, overt attention, language, executive function, etc.). In this review, all SES effects on ERPs appeared to reflect an impairment or a less efficient form of task-related neural activity for low-SES compared to high-SES individuals. Overall, these results confirm that a wide variety of distinct neural processes with different functional meanings are sensitive to SES differences. The findings of this review also suggest that the relationship between SES and some ERP components may depend on the developmental stage of study participants. Results are further discussed in terms of the current limitations of this field and future avenues of research.